Comparative Analysis of Semi Basement Wall With Different Cohesion and Basement Depth in West Jakarta - Luthfy Alfarizi; Resi Aseanto (NAROTAMA UNIVERSITY, Indonesia, 2021)
DKI Jakarta has a population density of 19,516 people / square km. Government of Jakarta in the PERDA DKI Jakarta No. 7-2010 CHAPTER 5 Article 42 Paragraph 1 states that